What Should We Agree on about the Repugnant Conclusion?. Issue 4 (December 2021) - Zuber, Stéphane; Venkatesh, Nikhil; Tännsjö, Torbjörn; Tarsney, Christian; Stefánsson, H. Orri; Steele, Katie; Spears, Dean; Sebo, Jeff; Pivato, Marcus; Ord, Toby; Ng, Yew-Kwang; Masny, Michal; et al.
Abstract : The Repugnant Conclusion is an implication of some approaches to population ethics. It states, in Derek Parfit's original formulation, For any possible population of at least ten billion people, all with a very high quality of life, there must be some much larger imaginable population whose existence, if other things are equal, would be better, even though its members have lives that are barely worth living. (Parfit 1984: 388)